Search for new physics with same-sign isolated dilepton events with jets and missing transverse energy at the LHC - Chatrchyan, S. (2011)
The results of searches for new physics in events with two same-sign isolated leptons, hadronic jets, and missing transverse energy in the final state are presented. The searches use an integrated luminosity of 35 pb(-1) of pp collision data at a centre-of-mass energy of 7TeV collected by the CMS experiment at the LHC. The observed numbers of events agree with the standard model predictions, and no evidence for new physics is found. To facilitate the interpretation of our data in a broader range of new physics scenarios, information on our event selection, detector response, and efficiencies is provided.